A Substitution-Box Structure Based on Solar Panel Data - Turan, Esin; Ozdemir, Mustafa Kemal; Karakaya, Barış; Özkaynak, Fatih (My University, 2022)
The demonstration that the nonlinearity criterion of substitution box (s-box) structures based on the random selection principle can be improved through post-processing techniques has created a new research area. The necessity of obtaining sbox structures that can be given as input to these post-processing algorithms has emerged. In this study, a study was carried out on how to obtain sbox structures based on solar panel data. The cryptological properties of the obtained sbox structures were tested using five basic evaluation metrics and compared with similar studies in the literature. The successful results indicated that these outputs may have various practical applications in the future.
Keywords: Chaos; Substitution box; random selection; block cipher